Protective Effects of Jujubosides on 6-OHDA-Induced Neurotoxicity in SH-SY5Y and SK-N-SH Cells - Chao-Hsuan Chen; Pei-Chen Hsu; Shih-Wei Hsu; Kun-Ting Hong; Kai-Yuan Chen; Jie-Long He; Der-Yang Cho; Yun-Chi Wang; Wen-Shin Chang; Da-Tian Bau; Chia-Wen Tsai (Molecules, 2022)
6-hydroxydopamine (6-OHDA) is used to induce oxidative damage in neuronal cells, which can serve as an experimental model of Parkinson’s disease (PD). Jujuboside A and B confer free radical scavenging effects but have never been examined for their neuroprotective effects, especially in PD; therefore, in this study, we aimed to investigate the feasibility of jujubosides as protectors of neurons against 6-OHDA and the underlying mechanisms. 6-OHDA-induced neurotoxicity in the human neuronal cell lines SH-SY5Y and SK-N-SH, was used to evaluate the protective effects of jujubosides. These findings indicated that jujuboside A and B were both capable of rescuing the 6-OHDA-induced loss of cell viability, activation of apoptosis, elevation of reactive oxygen species, and downregulation of the expression levels of superoxide dismutase, catalase, and glutathione peroxidase. In addition, jujuboside A and B can reverse a 6-OHDA-elevated Bax/Bcl-2 ratio, downregulate phosphorylated PI3K and AKT, and activate caspase-3, -7, and -9. These findings showed that jujubosides were capable of protecting both SH-SY5Y and SK-N-SH neuronal cells from 6-OHDA-induced toxicity via the rebalancing of the redox system, together with the resetting of the PI3K/AKT apoptotic signaling cascade. In conclusion, jujuboside may be a potential drug for PD prevention.